PERAN JAMINAN KESEHATAN TERHADAP PEMANFAATAN TENAGA KESEHATAN SEBAGAI PENOLONG PERSALINAN DI INDONESIA (ANALISIS DATA SUSENAS 2017) - Farida Kusumaningrum; Prastuti Soewondo (Puslitbang Upaya Kesehatan Masyarakat, 2018)
Background: The global maternal mortality ratio in 2015 was 216 deaths per 100,000 live births due to complications during pregnancy and delivery. The utilization of birth attendants is one of the important indicators that play a role for increasing safe delivery so that it can prevent maternal and child mortality. Objective: Knowing the role of health insurance and other related factors towards the utilization of skilled birth attendants in Indonesia. Method: This study uses Susenas data in 2017 with the sample size of 38,485 reproductive age women. The analysis uses logistic regression with the Logit model. Result: The logit test results show that the model is able to explain the data of 9.93 percent. Prob> Chi2 significance value of 0,000 means that all independent variables have a significant effect on the dependent variable. Women who had health insurance were 1,351 times higher to use skilled birth attendant at delivery. Conclusion: The Ownership of health insurance has a significant role towards the utilization of skilled birth attendants in Indonesia in 2017. Likewise with other related factors including increasing age, education ≥ SLTA, urban living areas, parity ≤ 3 people, and economic status in quintiles 2, 3, 4 and 5.